RPC-PET: status and perspectives - Couceiro, M. (2007)
The status of the RPC-PET technology for small animals is briefly reviewed and its sensitivity performance for human PET studied through Monte-Carlo simulations. The cost-effectiveness of these detectors and their very good timing characteristics open the possibility to build affordable TOF-PET systems with very large fields of view. Simulations suggest that the sensitivity of such systems for human wholebody screening, under reasonable assumptions, may exceed the present crystal based PET technology by a factor up to 20.